Design of a Lean Manufacturing model to reduce order delivery in a Textile Mype - Liza Ludeña, Bertha (2022)
This Mype has as its main problem the delay time in the delivery of its security clothing orders. Faced with the problem, it is intended to present a solution whose objective is the elaboration of a model design applying Lean Manufacturing tools that allows the reduction of times in the production processes, in the same way to increase the productivity indicator in safety vest garments and rompers Consequently, tools will be applied, such as: A value stream map (VSM) as a diagnostic tool, and the 5s, SMED, Poka Yoke and Kanban as an opportunity to improve process management. The main result of improvement when implementing this model based on lean manufacturing was the reduction of order delivery time by 10%. On the other hand, an improvement in the production process of the sewing area was perceived by 50.37% and a reduction in tool change time of a single digit of minutes in 22.05 minutes.